Clinical features of GH deficiency and effects of 3 years of GH replacement in adults with controlled Cushing's disease - Höybye, Charlotte; Ragnarsson, Oskar; Jönsson, Peter J; Koltowska-Häggström, Maria; Trainer, Peter; Feldt-Rasmussen, Ulla; Biller, Beverly M K (European journal of endocrinology, 2010)
ObjectivePatients in remission from Cushing's disease (CD) have many clinical features that are difficult to distinguish from those of concomitant GH deficiency (GHD). In this study, we evaluated the features of GHD in a large cohort of controlled CD patients, and assessed the effect of GH treatment.Design and methodsData were obtained from KIMS, the Pfizer International Metabolic Database. A retrospective cross-sectional comparison of background characteristics in unmatched cohorts of patients with CD (n=684, 74% women) and nonfunctioning pituitary adenoma (NFPA; n=2990, 39% women) was conducted. In addition, a longitudinal evaluation of 3 years of GH replacement in a subset of patients with controlled CD (n=322) and NFPA (n=748) matched for age and gender was performed.ResultsThe cross-sectional study showed a significant delay in GHD diagnosis in the CD group, who had a higher prevalence of hypertension, fractures, and diabetes mellitus. In the longitudinal, matched study, the CD group had a better metabolic profile but a poorer quality of life (QoL) at baseline, which was assessed with the disease-specific questionnaire QoL-assessment of GHD in adults. After 3 years of GH treatment (mean dose at 3 years 0.39 mg/day in CD and 0.37 mg/day in NFPA), total and low-density lipoprotein cholesterol decreased, while glucose and HbAlc increased. Improvement in QoL was observed, which was greater in the CD group (−6 CD group versus −5 NFPA group, P<0.01).ConclusionIn untreated GHD, co-morbidities, including impairment of QoL, were more prevalent in controlled CD. Overall, both the groups responded similarly to GH replacement, suggesting that patients with GHD due to CD benefit from GH to the same extent as those with GHD due to NFPA.